FEATURES OF miRNA ASSOCIATIONS WITH mRNA OF MYOCARDIAL INFARCTION CANDIDATE GENES - Mukushkina Dina Daurenbekovna,; Ivashchenko Anatoliy Timofeevich,; Siegfried Labeit, (Academic Journal of Physical and Chemical Sciences, 2021)
Cardiovascular diseases, in particular myocardial infarction, are one of the most common causes of death in the world. To date, the risk assessment strategy infarction and post-infarction complications represent a significant problem sensitivity and predictive value of modern methods and markers, so the identification of new genetic markers is an actual problem. In this research, functionally significant candidate genes were studied, which are involved in the processes associated with the pathogenesis of myocardial infarction, in lipid metabolism, thrombus formation, endothelial dysfunction, and inflammatory reactions. However, in addition to genes, it has been determined that miRNA is also involved in the development of myocardial infarction by regulating the expression of target genes. This paper presents characteristics of miRNA interactions with mRNAs of candidate myocardial infarction genes. We have identified 34, 51 and 36 target genes that have miRNA binding sites in the 5'UTR, CDS, and 3'UTR regions, respectively. Based on the criteria chosen in our study, candidate genes were identified that have a free energy of interaction with miRNA equal to -120 kJ/mole and higher in the following associations: in 5’UTR - ID02142.3p-miR and ALDH2; ID00909.3p-miR and ALOX5; ID00216.3p-miR and CD40; ID01272.3p-miR and DDAH2; ID01774.5p-miR and IL6R; miR-6752-5p and KLF4; ID03332.3p-miR and LAMA3; ID02363.5p-miR and NOS3; ID02800.3p-miR and OPA1; ID01310.3p-miR and PDE4D; ID03397.3p-miR and PTGS2; ID01098.3p-miR and SERPINE1; ID01018.3p-miR and SGPP1; ID02430.3p-miR and SHH; ID01652.3p-miR and THBS1; ID01770.3p-miR and ZNF202; in CDS - ID00457.3p-miR and APOA1; ID00425.5p-miR and BTN2A1; ID01632.5pmiR and CCL5; ID02899.3p-miR and CDKN2B; miR-6894-5p and CYP1A2; ID01806.3p-miR and IL6R; ID01403.5p-miR and PLAUR; ID02950.3p-miR and SEMA3F; ID03332.3p-miR and SGPP1; ID02062.3p-miR and SIRT6; ID02050.3p-miR and TNF; ID01804.3p-miR and XBP1; ID00182.5p-miR and ZNF202; in 3’UTR - ID01293.5p-miR and SMTN; ID01882.5p-miR and TNNI3. The identified associations can be used as genetic markers in the diagnosis of myocardial infarction.